A populist reader. Selections from the works of American populist leaders [= H. Garland, W. Scott Morgan, N.B. Ashby a.o.]. Ed. by G. Brown Tindall (Harper & Row, 1966)
American Perspectives. Ed. by B. Wishy and W.E. Leuchtenburg.